Exploring the role of polysaccharides in mitigating organ damage caused by pesticide-induced toxicity: A systematic review and meta-analysis of in vivo studies - Sakinah, Elly N.; Diniyah, Nurud; Subagio, Achmad; Marchianti, Ancah CN.; Firdaus, Jauhar; Fambudi, Stela S.; Amini, Stefia A.; Putri, Dhiani E. (Narra J, 2025)
Although polysaccharides have demonstrated potential in alleviating dysbiosis, the overall impact of polysaccharides on minimizing oxidative stress and organ damage in vivo has not been thoroughly investigated. The aim of this study was to investigate the comprehensive effects of polysaccharides in mitigating pesticide toxicity in animal studies, focusing on biomarkers related to oxidative stress, antioxidant activity, kidney injury, lipid profiles, liver function, and the preservation of liver and kidney weights. A systematic search was conducted across nine indexed databases, including PubMed, Cochrane CENTRAL, Taylor & Francis, Scopus, Sage, EBSCO, ProQuest, ScienceDirect, and Google Scholar. Rayyan.ai was used to screen in vivo studies that met the predefined inclusion and exclusion criteria. The quality of the selected in vivo studies was evaluated using SYRCLE’s Risk of Bias tool, specifically designed for animal studies. Thirteen randomized animal studies, comprising 330 mice and rats, were included in the analysis. The findings revealed that polysaccharides significantly increased antioxidant levels, including catalase (CAT) (p<0.00001), superoxide dismutase (SOD) (p<0.00001), glutathione peroxidase (GPx) (p<0.00001), and reduced glutathione (GSH) (p<0.00001). Polysaccharides also significantly reduced oxidative stress markers, such as malondialdehyde (MDA) (p<0.00001) and nitric oxide (NO) (p<0.0001), as well as kidney injury biomarkers, including serum creatinine (p<0.00001) and urea (p<0.00001). Additionally, improvements in lipid profiles were observed, with significant reductions in triglycerides (TG) (p=0.04) and total cholesterol (TC) (p<0.00001). However, there were no significant differences in high-density lipoprotein (HDL) (p=0.28) and low-density lipoprotein (LDL) (p=0.32) levels. Polysaccharides significantly alleviate liver biomarkers, including aspartate transaminase (AST) (p<0.0001), alanine transaminase (ALT) (p<0.005), and alkaline phosphatase (ALP) (p<0.0001). Polysaccharides also contributed to the maintenance of liver weight (p=0.009), although no significant differences were observed in kidney weights (p=0.81). The study highlights that polysaccharides exert significant effects in enhancing antioxidant levels, reducing oxidative stress and organ damage biomarkers, and preserving liver weights.